Residual stress of high strength steel box T-joints Part 1 : experimental study - Jiang, Jin (2014)
In Part 1 of this study, an experimental investigation on the residual stress distributions near the weld toe of high strength steel box section T-joints is conducted. Two specimens fabricated by welding at ambient temperature and at a preheating temperature of 100°C were studied. The effects of preheating on the residual stress distribution near the weld toe of the T-joints were investigated by applying the standard ASTM hole-drilling method. A study was also conducted to evaluate the corner effect of the welding and the brace-to-chord width ratio of the box section T-joint on the residual stress distribution near the weld toe of the T-joint.